PENGEMBANGAN MEDIA KAROGAN BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN IPAS KELAS IV SD INPRES 12/79 LONRAE KABUPATEN BONE - Ananda, Nur Aisyah Ananda; Satriani, Satriani; Asriadi, Asriadi (MACCA : Science-Edu Journal, 2025)
This research is a development research or also known as Research and Development (R&D) using a modified ADDIE development model design with 3 stages consisting of Analysis, Design, and Development. The purpose of this study is to determine the needs analysis, development of Karogan media based on Augmented Reality in Science Learning and to determine the validation of Karogan based on Augmented Reality in Science Learning. This study uses qualitative and quantitative data analysis techniques. Qualitative analysis includes descriptions of observation results, interviews, validator suggestions that are analyzed descriptively for product improvement. Meanwhile, quantitative analysis assesses the feasibility of the product based on expert, teacher, and student assessments. This study has succeeded in developing Augmented Reality Learning Media in Science Learning for Grade IV Elementary School known as Karogan. The study shows that the learning media developed is included in the category of feasible and appropriate for use by students and teachers in the learning process after going through the validation process. This development product not only provides an alternative innovative learning media, but also has implications for the transformation of technology-based Science learning, where the integration of Augmented Reality (AR) can increase interactivity, conceptual understanding, and student learning motivation more effectively.